Exposure assessment to essential elements through the consumption of canned fish in Serbia - J. Petrovic; M. Jovetic; M. Štulić; A. Redžepović-Đorđević; D. Vujadinović; I. V. Djekic; I. B. Tomasevic (Теория и практика переработки мяса)
The aim of this study was to provide a quantitative exposure assessment to essential elements through the consumption of canned fish in Serbia. This objective was fulfilled by analyzing content of essential elements in canned fish and by using data from a food consumption survey. Consumption survey of canned fish was designed and performed to general principles and EFSA guidelines on data collection of national food consumption. The questionnaire was performed on 1,000 respondents during 2018. Determination of copper, zinc and iron levels were performed on 454 canned fish and seafood samples divided into four groups (canned tuna, canned sardines, canned other sea fish and canned seafood) during five consecutive years (2014–2018). This study showed significant association between sex, BMI and weight and consumption patterns. Obtained average weekly consumption of canned fish confirms our assumption that consumption of canned fish is significant in Serbia. Zinc and iron were found in all 454 samples (100%), and copper in 222 samples (48.9%). The average obtained concentration in all samples were 1.268 mg kg–1 for Cu, 5.661 mg kg–1 for Zn and 9.556 mg kg–1 for Fe. The highest concentration for all three minerals were found in canned sardines (Cu — 6.49 mg kg–1, Zn — 37.2 mg kg–1 and Fe — 21.8 mg kg–1). Obtained mean exposure to intake of copper, zinc and iron from canned fish was 1.2241 μg/kg bw/day, 5.4634 μg/kg bw/day and 9.2231 μg/kg bw/day, respectively. Exposure of Serbian population to zinc, copper, and iron through consumption of canned fish is less than recommended daily reference intakes and there is no risk of reaching toxic levels by consuming fish.